SISTEM PENDUKUNG KEPUTUSAN PRIORITAS PENAGIHAN ANGSURAN DALAM BENTUK MICROSERVICE - Muhammad Faiz Azam; Neny Rosmawarni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
Economic downturn due to the COVID-19 pandemic has caused delays in payment of union’s credits installments and has experienced bad credits. To overcome this, it is necessary to conduct collection that is right on target according to priority. To simplify and increase the accuracy of priorities of the collection, it would be better if the priority determination was automated using a Decision Support System (DSS). The DSS needs to be able to process variable determinants, because invoice collection priority conditions may change depends on the situation. The DSS also needs to can be implemented in all of union’s application systems or union’s information systems, which can be different with each union. The making of applications in this study using the RAD (Rapid Application Development) method, and for the DSS method this study using SAW (Simple Additive Weighting) for the method. By using Node JS this research produce application that is microservice by utilizing REST API technology.